To find new markers for poor recovery of inflammatory bowel disease based on intestinal barrier function and inflammatory stress response markers - Lin, Renjing; Yang, Zongliang (Journal of Medical Biochemistry, 2026)
Objective: Inflammatory bowel disease (IBD) is one of the common diseases in the department of gastroenterology. We conducted a cross-sectional study on 74 cases of IBD admitted to our hospital from January 2024 to April 2025, with a focus on the changes of serum cytokines in the patients. Subsequently, based on these cytokines, we developed a novel risk model for poor recovery in IBD. Methods: Based on the estimation of sample size and the screening of inclusion and exclusion criteria, we included 74 IBD patients as the research subjects (January 2024 to April 2025) for a cross-sectional survey. Key indicators were measured, including intestinal barrier markers (I-FABP, DAO, FC), inflammatory cytokines (IL-6, TNF-α, IL-10), Th17/Treg ratio, and stress hormones (Cor, ACTH). Subsequently, Logistic regression analysis was used to establish a risk model for predicting poor recovery of patients. Results: Patients with IBD have obvious intestinal barrier function impairment: intestinal barrier integrity makers—I-FABP, DAO, and FC—declined by 31.42%, 45.11%, and 37.31%, respectively (P<0.05). In addition, the patient also had a significant inflammatory response, but it decreased after treatment: inflammatory modulation improved, characterized by a rise in IL-10 and declines in IL-6, TNF-α, and the Th17/Treg ratio (P<0.05). Finally, the patient’s stress response was significant and relieved after treatment: Cor and ACTH decreased after treatment (P<0.05). After follow-up, 25 patients had poor recovery. Logistic regression analysis showed that ACTH was an independent factor affecting the poor recovery of IBD patients. ROC curve showed that the sensitivity and specificity of ACTH in predicting poor recovery of IBD were 79.59% and 68.00% (AUC=0.710), respectively. Conclusion: Patients with IBD have obvious intestinal barrier function impairment, and their inflammatory and stress responses are intensified. After the treatment, all these conditions improved. The detection of ACTH can effectively judge the recovery of IBD.